"I'll do anything to maintain my health": How women aged 65–94 perceive, experience, and cope with their aging bodies. (June 2017) - Bennett, Erica V.; Hurd Clarke, Laura; Kowalski, Kent C.; Crocker, Peter R.E.
Highlights: Women were accepting yet also critical of their body's functionality and appearance. Women engaged in appearance management to retain their youthfulness and femininity. Body functionality was managed through physical activity and healthy eating. Women engaged in upward and downward aging body-related social comparisons. Self-compassion for the aging body was perceived as idealistic and contextual. Abstract: We explored how physically active women perceived, experienced, and coped with their aging bodies, and examined their perceptions of the utility of self-compassion to manage aging body-related changes. Findings from a thematic analysis of interviews with 21 women aged 65–94 revealed that they were appreciative of how their bodies worked and accepting of their physical limitations, yet concurrently critical of their body's functionality and appearance. Participants engaged in physical activity and healthy eating to maintain their health and body functionality, yet also used diet, hair styling, anti-aging creams, makeup, physical activity, and clothing to manage their appearances. To assess their bodies (in)adequacies, they engaged in upward or downward social comparisons with others their age. Participants perceived self-compassion for the aging body to be idealistic and contextual. Findings highlight the importance of health and body functionality in influencing the cognitive, emotional, and behavioral management of the aging body.